The way I feel - Cain, Janan (Seattle, Wash. : Parenting Press, 2000)
Illustrations and rhyming text portray children experiencing a range of emotions, including frustration, shyness, jealousy, and pride.
Keywords: Emotions -- Juvenile literature; Emotions